Phenotypic Evaluation of Barley Landraces (Hordeum vulgare L.) for Resistance to Net-Form Net Blotch Disease (Pyrenophora teres f. teres) - El Herch, Chaimae; Al-Jaboobi, Muamar; Tsivelikas, Athanasios; Kehel, Zakaria; Koussa, Tayeb; Kemal, Seid Ahmed; Faize, Mohamed (2024)
Globally cultivated on 49 million hectares, barley ranks fourth after maize, rice, and wheat. Dubbed the 'climate change crop', it thrives in extreme conditions, requires minimal resources, provides consistent yields, and is a key food and livestock feed source in many developing countries (Pesaresi, 2020). The foliar disease, Net Form Net Blotch, caused by Pyrenophora teres f. teres, limits barley production by reducing grain yield, quality, and straw. Global yield losses approach 40%, and in Morocco, it's up to 29%, especially in susceptible cultivars (Afanasenko et al., 2022 ; Jebbouj et El Yousfi, 2006). Fungicides are one of the common methods used to minimize the effects of net blotch, but they pose issues like high costs, environmental concerns, and the emergence of resistant pathogen strains (Alaoui & El Aissami, 2014). Effective management requires exploring alternatives: Resistant barley cultivars emerge as an environmentally and economically sustainable approach (Abebe, 2021).